Preliminary Study on the Mechanism of Chitosan and ε-Polylysine Inhibition against Carbibacterium divergens - Weiying HUANG; Xiaoting LIU; Yufeng GUAN; Yihui WU; Canye FAN; Qiaoyu LIU; Haiguang CHEN; Junshi WU; Xiaoyu WANG (Shipin gongye ke-ji, 2024)
To investigate the effects of chitosan and ε-polylysine on the cell structure and cytoprotective enzymes of Carbibacterium divergens to explore their inhibition mechanism against Carbibacterium divergens, the broth dilution method was used to determine the minimum inhibitory concentrations (MICs) of chitosan and ε-polylysine against Carbibacterium divergens. Their effects on the cellular structure of Carbibacterium divergens were then assessed by several indexes, such as growth curves, electronic conductivity, extracellular nucleic acids, extracellular proteins, and alkaline phosphatase (AKP) activity, and the microstructure of bacteria were also observed by scanning electron microscopy (SEM). In addition, their role in oxidative stress was analyzed by detecting changes in catalase (CAT) activity and superoxide dismutase (SOD) activity. The results showed that the MIC of chitosan and ε-polylysine against Carbibacterium divergens was 0.1953 and 0.1563 mg/mL, respectively. The intracellular components (AKP, proteins, nucleic acids, and ions) leaked after treatment with MIC and 2MIC chitosan and ε-polylysine. The mass concentrations of chitosan and ε-polylysine were negatively correlated with enzyme activity, and the activities CAT and SOD significantly decreased (P<0.05). Scanning electron microscopy showed that chitosan could deform the cell and its contents oozed out, while ε-polylysine caused the cell to fold and distort, forming holes on the cell surface. In summary, both chitosan and ε-polylysine can inhibit the growth of Carbibacterium divergens by destroying cell wall, damaging cell membrane and generating oxidative stress reaction.